Energy and Area Costs of Lightweight Cryptographic Algorithms for Authenticated Encryption in WSN - Lara-Nino, Carlos Andres; Morales-Sandoval, Miguel; Diaz-Perez, Arturo (Security and communication networks, 2018)
Wireless Sensor Networks (WSN) aim at linking the cyber and physical worlds. Their security has taken relevance due to the sensitive data these networks might process under unprotected physical and cybernetic environments. The operational constraints in the sensor nodes demand security primitives with small implementation size and low power consumption. Authenticated encryption is a mechanism to provide these systems with confidentiality, integrity, and authentication of sensitive data. In this paper we explore hardware implementation alternatives of authenticated encryption through generic compositions, to assess the costs of this security approach in WSN. Two symmetric ciphers, AES and Present, and two hash functions, SHA and spongent, are used as the underlying primitives for the generic compositions. All the architectures studied in this work are implemented and evaluated in an FPGA-based WSN mote. The life time of the sensor node is used as the main evaluation metric but FPGA resources are also reported. From the experimental results obtained, it is shown how lightweight ciphers significantly contribute to reduce implementation area and energy consumption overheads, extending the lifetime of the sensor node.